Sharing ideas between cultures with videos - Bentley, J.; Mele, P. van (Informa UK Limited, 2011)
Civil servants, agricultural researchers, extension people and media experts often think that videos for farmers need to be filmed locally, so that the audience identifies with the actors. But this is not so. Farmers in southwestern and northern Nigeria reacted to videos on rice seed health (made in Bangladesh), on parboiling (filmed in Benin) and rice cultivation(from Mali). The farmers criticized the videos freely, but their remarks were about the technical pros and cons of thetechnologies presented in the videos. The farmers had no preference for watching videos featuring West African orBangladeshi actors. The farmers only cared about the technical content of the film. This is an important, practicalconclusion, because it is much easier and cheaper to dub a film into a second language than to film it over again.